Linkage disequilibrium and diversity for three genomic regions in Azoreans and mainland Portuguese - Branco, C.C. (2009)
Studies on linkage disequilibrium (LD) across the genome and populations have been used in recent years with the main objective of improving gene mapping of complex traits. Here, we characterize the patterns of genetic diversity of HLA loci and evaluate LD (D') extent in three genomic regions: Xq13.3, NRY and HLA. In addition, we examine the distribution of DXS1225-DXS8082 haplotype diversity in Azoreans and mainland Portuguese. Allele distribution has demonstrated that the São Miguel population is genetically very diverse; haplotype analysis revealed 100% discriminatory power for X- and Y-markers and 94.3% for HLA markers. Standardized multiallelic D' in these three genomic regions shows values lower than 0.33, thereby suggesting there is no extensive LD in the São Miguel population. Data regarding the distribution of DXS1225-DXS8082 haplotypes indicate that there are no significant differences among all the populations studied, (Azorean geographical groups, the Azores archipelago and mainland Portugal). Moreover, in these as well as in other European populations, the most frequent DXS1225-DXS8082 haplotype is 210-219. Even though São Miguel islanders and Azoreans do not constitute isolated populations and show LD for only very short physical distances, certain characteristics, such as the absence of genetic structure, the same environment and the possibility of constructing extensive pedigrees through church and civil records, offer an opportunity for dissecting the genetic background of complex diseases in these populations.